Mobility limitations and fear of falling in non-English speaking older Mexican-Americans. Issue 5 (3rd September 2017) - James, Eric G.; Conatser, Phillip; Karabulut, Murat; Leveille, Suzanne G.; Hausdorff, Jeffrey M.; Cote, Sarah; Tucker, Katherine L.; Barton, Bruce; Bean, Jonathan F.; Al Snih, Soham; Markides, Kyriakos S.
ABSTRACT: Objective: To determine whether older Mexican-Americans who cannot speak and/or understand spoken English have higher rates of mobility limitations or fear of falling than their English-speaking counterparts. Design: We conducted a cross-sectional analysis of 1169 community-dwelling Mexican-Americans aged 72–96 years from the 2000–2001 wave of the Hispanic Established Population for the Epidemiological Study of the Elderly. Mobility limitations were defined as having a Short Physical Performance Battery score ≤9, and fear of falling by participant report of being somewhat, fairly, or very afraid of falling. We determined the rates and odds ratios, for having mobility limitations and fear of falling as a function of English ability in those who were 72–96, <80, and ≥80 years of age. Results: Among participants who were unable to speak and/or understand spoken English 85.7% had mobility limitations and 61.6% were afraid of falling, compared to 77.6% and 57.5%, respectively, of English speakers. Before adjusting for covariates, participants who did not speak and/or understand spoken English were more likely to have mobility limitations (odds ratio: 1.7; 95% CI: 1.3–2.4) but not fear of falling, compared to English speakers. Among those aged ≥80 years, but not those <80 years, who did not speak or understand English were more likely to have mobility limitations (odds ratio: 4.8; 95% CI:2.0–11.5) and fear of falling (odds ratio: 2.0; 95% CI:1.3–3.1). Conclusion: Older Mexican-Americans who do not speak or understand spoken English have a higher rate of mobility limitations and fear of falling than their English-speaking counterparts.